Islamic Finance And Conventional Finance Organic Relationship And Individual Differentiative Aspects - Karimjonova Munavvar Ibragimovna; Ruzinov Bakhtiyor Muhammad Ogli (Euro Asian Journal Publishing, 2024)
This article covers the principles, mechanisms and importance of Islamic finance and conventional financial systems. Also, the interrelationship and differences of traditional finance and Islamic finance, their role in the countryʼs economy in the conditions of the market economy are revealed
Keywords: financial system; conventional finance; private sector